Elective surgical versus conservative management of complicated diverticulitis: A systematic review and meta‐analysis. Issue 2 (8th February 2022) - Yeow, Marcus; Syn, Nicholas; Chong, Choon Seng
Abstract : Objectives: There is no consensus on the optimal treatment for patients with complicated diverticulitis. In this systematic review and meta‐analysis we aimed to determine the indications for elective surgery in complicated diverticulitis by comparing conservative treatment with elective surgery. Methods: A meta‐analysis of recurrence, morbidity and stoma rates was performed using a random effects model. Patient‐reported quality of life (QoL) and cost‐effectiveness outcomes were synthesized qualitatively. Results: Eleven randomized controlled trials and non‐randomized studies with a total of 7415 patients were included. In statistical terms, the recurrence of diverticulitis was significantly higher in the conservatively treated group than in the elective surgery group (odds ratio [OR] 0.24, 95% confidence interval [CI] 0.12‐0.51). The stoma rate (OR 2.34, 95% CI 1.88‐2.92) and the morbidity rate (OR 4.29, 95% CI 2.24‐8.23) were significantly higher in the elective surgery group than in the conservatively treated group. There was some evidence for a significant increase in QoL and long‐term cost‐effectiveness in the elective surgery group than in the conservatively treated group. Conclusions: Indications for elective surgery should not include the prevention of emergency colostomy or complications. Elective surgical resection may be considered in patients with complicated diverticulitis with the goal of improving their QoL and long‐term cost‐effectiveness. Abstract : There is no consensus on the optimal treatment for patients with complicated diverticulitis. In this systematic review and meta‐analysis, it was found that indications for elective surgery should not include the prevention of emergency colostomy or complications. Elective surgical resection may be considered in patients with complicated diverticulitis with the goal of improving their quality of life and long‐term cost‐effectiveness. Abbreviation: CI, confidence interval